Co-morbidities and outcome of childhood psychogenic non-epileptic seizures––An observational study. (February 2015) - Rawat, Vikram Singh; Dhiman, Vikas; Sinha, Sanjib; Vijay Sagar, Kommu John; Thippeswamy, Harish; Chaturvedi, Santosh Kumar; Srinath, Shoba; Satishchandra, Parthasarthy
Highlights: Diagnoses and outcome of 34 children with PNES were evaluated. Most common psychiatric diagnosis was dissociative disorder ( n  = 34, 77.3%). Other diagnoses were ADHD, gratification disorder, night terror. Co-morbid psychiatric disorders were present in 17 children (50%). Good outcome was noted in 76.5% children. Abstract: Purpose: To assess the psychiatric diagnoses and outcome in children with psychogenic non-epileptic seizures (PNES). Methodology: This hospital based observational study was performed on 44 children aged <16 years, who suspected to have psychogenic non-epileptic seizures based on video-EEG, from August 2005 to August 2012. The parameters noted were the psychiatric diagnosis, co-morbidities, management assessment and interventions (pharmacological and psychosocial), number and duration of follow-up visits, symptoms at follow-up, functioning as reflected by involvement in the social and scholastic work. Results: All forty four children completed the evaluation. Thirty four children were diagnosed as having PNES and the underlying psychiatric diagnosis was conversion disorder ( n  = 34, 77.3%). Co-morbid psychiatric disorders were present in 17 children (50%). The common co-morbidities were intellectual disability ( n  = 8, 23.5%), specific learning disorder ( n  = 5, 14.7%), and depression ( n  = 5, 14.7%). Co-morbid epilepsy was present in 8 (23.5%) children and family history of epilepsy was present in 10 (29.4%) cases. About 17 of 34 (50.0%) patients had a minimum follow-up of 6 months (13.9 ± 4.8 months). Twenty six children (76.5%) remained symptom free at the follow-up of 9.8 ± 7 months. The remaining 10 children (22.7%) had non-epileptic seizures with underlying diagnosis of Attention Deficit Hyperactivity Disorder (ADHD), gratification disorder and other physiological conditions. Conclusions: Conversion disorder is a common diagnosis underlying psychogenic non-epileptic seizures. Outcome was good in 76.5% children with PNES. A multidisciplinary approach is needed in the diagnosis and management of PNES.